Corporate Governance and Expected Stock Returns: A Study of Companies listed in Kuala Lumpur Stock Exchange - Radhakrishnan Nair, Mohan Krishnan (2004)
Corporate governance is considered important among investors since it protects the investors against misappropriation by managers. The Capital Asset Pricing Model states that the expected rate of return for shareholders depends on the covariance risk with the market portfolio. However the existence of agency costs changes the situation. If agency costs exist, then better corporate governance can play a role in reducing the expected rate of return of shareholders as the shareholders auditing and monitoring costs are reduced. Thus this study attempts to explain the significance of firm specific corporate governance in explaining the expected stock returns in a cross section of firms in Malaysia. Constructing a Corporate Governance Score (CGS) for Malaysian companies, the study document an evidence of a negative relationship between expected returns and CGS when dividend yield is used as proxy for the cost of capital.However statistical testing using historical returns and price earnings ratio as proxies, does not provide enough evidence of a relationship between expected returns and CGS. The paper also studied the relationship between corporate governance and firm valuation using Market- to-book ratio as a measure of firm valuation. The results do not reveal evidence of a positive relationship between CGS and firm value. The findings are rationalized by the unique nature of Malaysian capital market, weak legal protection and disclosure rules, ownership structure of Malaysian firms and by the investor’s perception of corporate governance in emerging markets.